Eponyms associated with the nomenclature of the recent species of rhinoceros - Rookmaaker, Kees (Pachyderm, 2021)
Since 1758, a total of 16 eponyms have been described to honour explorers and taxonomists for the recent species of rhinoceros. This paper presents short biographies and the circumstances of the description of these names used in zoological nomenclature. The name blythii was named after Edward Blyth (1810–1873), brucii after James Bruce (1730–1794), burchellii after William John Burchell (1781–1863), Campbell’s rhinoceros after John Campbell (1766–1840), camperis, camperii, camperi after Petrus Camper (1722–1789), cottoni after Percy Horace Gordon Powell-Cotton (1866–1940), crossii after Edward Cross (1774–1854), floweri after William Henry Flower (1831–1899), gordoni after Robert Jacob Gordon (1743–1795), harrissoni after Tom Harrisson (1911–1976), holmwoodi after Frederick Holmwood (d.1896), jamrachi after William Jamrach (1842–1923), michaeli after Michael Grzimek (1934–1959), and oswelli after William Cotton Oswell (1818–1893). Résumé Depuis 1758, un total de 16 éponymes ont étés décrits pour honorer les explorateurs et les taxonomistes des espèces récentes de rhinocéros. Cet article présente de brèves biographies et les circonstances liées à la description de ces noms utilisés dans la nomenclature zoologique. Le nom blythii a été nommé d’après Edward Blyth (1810–1873), brucii d’après James Bruce (1730–1794), burchellii d’après William John Burchell (1781–1863), le rhinocéros de Campbell d’après John Campbell (1766–1840), camperis, camperii, camperi d’après Petrus Camper (1722–1789), cottoni d’après Percy Horace Gordon Powell-Cotton (1866–1940), crossii d’après Edward Cross (1774–1854), floweri d’après William Henry Flower (1831–1899), gordoni d’après Robert Jacob Gordon (1743–1795), harrissoni d’après Tom Harrisson (1911–1976), holmwoodi d’après Frederick Holmwood (décédé en 1896), jamrachi après William Jamrach (1842–1923), michaeli d’après Michael Grzimek (1934–1959) et oswelli d’après William Cotton Oswell (1818–1893).